Treatment of Palatal Myoclonus with Botulinum Toxin Injection - Mursalin M. Anis; Natasha Pollak (Case Reports in Otolaryngology)
Palatal myoclonus is a rare cause of pulsatile tinnitus in patients presenting to the otolaryngology office. Rhythmic involuntary contractions of the palatal muscles produce the pulsatile tinnitus in these patients. Treatment of this benign but distressing condition with anxiolytics, anticonvulsants, and surgery has been largely unsuccessful. A few investigators have obtained promising results with botulinum toxin injection into the palatal muscles. We present a patient with palatal myoclonus who failed conservative treatment with anxiolytics. Unilateral injection of botulinum toxin into her tensor veli palatini muscle under electromyographic guidance resolved pulsatile tinnitus in her ipsilateral ear and unmasked pulsatile tinnitus in the contralateral ear. A novel method of following transient postinjection symptoms using a diary is presented in this study. Botulinum toxin dose must be titrated to achieve optimal results in each individual patient, analogous to titrations done for spasmodic dysphonia. Knowledge of the temporal onset of postinjection side effects and symptomatic relief may aid physicians in dose titration and surveillance. We present suggestions on titrating the botulinum toxin dose to optimal levels. A review of the literature on the use of botulinum toxin for palatal myoclonus and some common complications are discussed.